American String Teachers Association Research Award 2019. Issue 1 (July 2020) - Barnes, Gail
This article is based on a speech that Barnes presented at a meeting of the Collegiate Roundtable at the American String Teachers Association 2019 National Conference in Albuquerque, New Mexico.